Asia's flying geese : how regionalization shapes Japan - Hatch, Walter, 1954- (Cornell studies in political economy., 2010)
"Asia's Flying Geese connects social organization, economics, and politics to bring the study of East Asian regionalism to life. In this landmark book on an extremely important topic, Walter F. Hatch explains Japan's economic stagnation and subsequent transformation by looking at its ties to East Asia."--Mark Tilton, Purdue University